Mechanical behaviour of Lac du Bonnet granite after high-temperature treatment using bonded-particle model and moment tensor. (July 2021) - Sun, Wei; Wu, Shunchuan; Xu, Xueliang
Abstract: The thermal cracking mechanism has been increasingly investigated to analyse and solve the mechanical behaviour of rocks in deep underground engineering. Classic laboratory tests bear the intrinsic limitation of non-repeatability and lack of direct observation of the interaction effect between thermal stresses and thermal micro-cracks. In this paper, the bonded-particle model and moment tensor is used to simulate the process of thermally induced micro-and macro-cracks in Lac du Bonnet granite to help provide insight into the detailed influence temperature on mechanical properties and acoustic emission characteristic of granite. During modelling, macro- and microscopic responses are quantified and compared against other laboratory data in the literature. The results indicate thermal stresses and thermally induced micro-cracks increase with increasing temperatures during heating, and cooling generally reduces the thermal stresses and increases the micro-cracks slightly. Grain-size distribution has a significant influence on thermal micro-cracks, thermal stress and the mechanical behaviours of granite. The increase in thermally induced tensile intergranular micro-cracks density mainly contributes to reduction of mechanical properties in granite samples subjected to heating–cooling cycles. It is also observed that the nature of sources and the b -value are associated with temperature, which gives some light on underground engineering in high temperature environments.